2023
DOI: 10.1080/09638288.2023.2176554
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare experiences among adults with hypermobile Ehlers-Danlos syndrome and hypermobility spectrum disorder in the United States

Abstract: This cross-sectional mixed-method study examined healthcare experiences among individuals in the US with hypermobile Ehlers-Danlos syndrome (hEDS) and hypermobility spectrum disorder (HSD), genetic connective tissue disorders. We hypothesized that many individuals with these conditions would report low satisfaction with healthcare and low health quality of life, and that lower healthcare satisfaction would be related to lower health-related quality of life and self-efficacy for symptom management.Methods: Adul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…A 2023 paper found that people with hEDS who report lower satisfaction with their healthcare providers experience a marked reduction in their healthrelated quality of life. This research also found that the most commonly reported theme when patients were asked about what changes they would make to improve healthcare services was improved education and awareness of hEDS and HSD among HCPs [70].…”
Section: "I Had Several Invasive Procedures That Probably Caused Me M...mentioning
confidence: 73%
“…A 2023 paper found that people with hEDS who report lower satisfaction with their healthcare providers experience a marked reduction in their healthrelated quality of life. This research also found that the most commonly reported theme when patients were asked about what changes they would make to improve healthcare services was improved education and awareness of hEDS and HSD among HCPs [70].…”
Section: "I Had Several Invasive Procedures That Probably Caused Me M...mentioning
confidence: 73%
“…A typical multidisciplinary team should include medical geneticists to confirm diagnosis, provide genetic counseling, and identify associated conditions; rheumatologists to evaluate and manage joint pain, instability, and other orthopedic issues; pain specialists to develop pain management strategies; physiotherapists to develop tailored exercise programs that minimize joint strain; neurologists to evaluate neurological symptoms and provide treatment for conditions such as headaches and neuropathic pain; psychiatrists to diagnose and medically manage mental health conditions through pharmacological interventions; psychotherapists and psychologists to develop coping strategies and lifestyle interventions for managing anxiety, depression, and other mental health challenges; gastroenterologists to assess and treat gastrointestinal issues such as dysmotility, nausea, vomiting, and abdominal pain; nutritionists to recommend dietary changes that may alleviate symptoms and promote overall health; hematologists to evaluate and manage easy bruising and excessive bleeding; and cardiologists to monitor for signs of vascular abnormalities, heart valve problems, and rhythm issues. Each specialist contributes unique expertise, perspectives and interventions that collectively aim to improve patients' quality of life by broadly targeting their multiple sources of suffering (Atwell et al, 2021; Demes et al, 2020; Estrella & Frazier, 2023; Spanhove et al, 2023; Yew et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the high frequency of comorbidities in chronic illnesses like chronic fatigue syndrome or hEDS/HSD present challenges for researchers trying to identify primary causes and effective treatments. Another Each specialist contributes unique expertise, perspectives and interventions that collectively aim to improve patients' quality of life by broadly targeting their multiple sources of suffering (Atwell et al, 2021;Demes et al, 2020;Estrella & Frazier, 2023;Spanhove et al, 2023;Yew et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with EDS may be misdiagnosed, poorly understood, and inadequately managed by healthcare professionals [ 16 , 17 ]. There are several common comorbid conditions, including: dysautonomia, postural orthostatic tachycardia syndrome (POTS), mast cell activation syndrome/disorder (MCAS/MCAD), craniocervical instability (CCI), anxiety, depression [ 18 ], migraine [ 19 ], gastrointestinal distress [ 20 ], temporomandibular joint disorder (TMJ), fibromyalgia, and arthritis [ 21 ], and in this paper these conditions will be referred to as “related disorders.” Patients with EDS therefore need clinical support from a wide range of medical experts.…”
Section: Introductionmentioning
confidence: 99%